Incidence of Oligohydramnios with Pregnancy Induced Hypertension - Maher, Amna; Salman, Nabila; Rafay, Ayesha; Almas, Muneeba; Hanfi, Rakhshanda; Chohan, Shazia (Indus Journal of Bioscience Research, 2025)
Introduction: The most common cause of decreased amniotic fluid during the third trimester of pregnancy is pregnancy with hypertensive disorders. The current study aims to ascertain the incidence of oligohydramnios in pregnancy-induced hypertension and the consequences that follow. Study design: Observational study. Settings: Department of Obstetrics & Gynaecology, National Engineering and Scientific Commission (NESCOM) Hospital, Islamabad, from July 2024 to February 2025. Methodology: As per protocol total 139 pregnant patients with hypertension brought on by pregnancy were registered in the study. All antenatal women were assessed and examined for hypertensive disorders. In the said population IUGR, premature rupture of membranes, twin and multiple pregnancy and women with antepartum hemorrhage were excluded as per exclusion criteria. After admission, a thorough history and examination was performed. Ultrasonography was performed to assess the liquor volume and diagnosis of oligohydramnios was made if AFI <5cm. All patients of the study were monitored till delivery and fetomaternal outcomes were recorded. Results: out of total 139 patients of PIH in the study group, thirty two (23.0%) had oligohydramnios. Maximum patients were primigravida (60%) and most patient were in age group between 32-40 years of age (52.51%). Cesarean section was the mode of delivery in 62.50% patients in this study group. Low birth weight was seen in 59.71% cases of study population and low APGAR score was found in 64.03%of cases. 17.99% neonates of this study group needed NICU admission. 2.15% had early neonatal death. Conclusion: Pregnancy outcomes can be improved and fetomaternal morbidity and mortality can be avoided with early detection and prompt treatment of oligohydramnios in pregnancies complicated with hypertensive disorders.